2006
DOI: 10.4067/s0716-97602006000300007
|View full text |Cite
|
Sign up to set email alerts
|

Histidines 13 and 14 in the Aβ sequence are targets for inhibition of Alzheimer's disease Aβ ion channel and cytotoxicity

Abstract: The fact that Alzheimer's beta amyloid (Aβ) peptides forms cation channels in lipid bilayers was discovered during the course of our experiments in the laboratory of "Guayo" Rojas at NIH in Bethesda, Maryland (USA). Recently, we found that the Aβ ion channel could be blocked selectively with small peptides that copy the amino acid sequence of the predicted mouth region of the Aβ channel pore. We now have searched for the essential amino acid residues required for this blocking effect by mutations. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 25 publications
3
44
0
1
Order By: Relevance
“…Thus the results lend further support to the hypothesis that the neurotoxic mechanism for A␤ is a direct consequence of the ability of A␤ to form calcium channels in the target neurons (33,45). These two compounds, however, do differ with respect to the reversibility of their interaction with A␤.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Thus the results lend further support to the hypothesis that the neurotoxic mechanism for A␤ is a direct consequence of the ability of A␤ to form calcium channels in the target neurons (33,45). These two compounds, however, do differ with respect to the reversibility of their interaction with A␤.…”
Section: Discussionsupporting
confidence: 68%
“…This is not the first instance in which compounds have been found that both block the Abeta channel and protect cells against Abeta neurotoxicity. In fact, previous data of this sort have contributed to the compelling support for the A␤ calcium channel hypothesis for the pathogenesis of Alzheimer's disease (45). However, with the exception of the other blocking compounds modeled after the amino acid sequences forming the mouth of the Abeta pore (34,(45)(46)(47)(48), the other inhibitors, such as Tris and Zn 2ϩ could be considered somewhat on the less potent side of the concentration/efficacy scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most believe that Aβ toxicity is linked to the formation of aggregated species, with the most toxic species being an intermediate between monomer and fibrils [11][12][13][14]. Some believe that Aβ acts via association with the cell membrane [15], to cause membrane depolarization, changes in membrane capacitance [16], membrane destabilization [17], pore formation [18,19] or free radical generation [20,21]. Consistent with these observations is that the first step in Aβ toxicity is Aβ binding to a membrane component.…”
Section: Introductionsupporting
confidence: 56%